2012
DOI: 10.1016/j.envsoft.2011.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of crop model predictions to entire meteorological and soil input datasets highlights vulnerability to drought

Abstract: Crop growth models are increasingly used as part of research into areas such as climate change and bioenergy, so it is particularly important to understand the effects of environmental inputs on model results. Rather than investigating the effects of separate input parameters, we assess results obtained from a crop growth model using a selection of entire meteorological and soil input datasets, since these define modelled conditions. Yields are found to vary significantly only where the combination of inputs m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…In this regard, some studies highlighted the importance of accurate modification of the crop growth parameters to increase the performance of the model (Zeleke et al 2011;Todorovic et al 2009). Several sensitivity analyses have shown the importance of soil water characteristics and available soil water for accurate crop growth and yield simulation under water stress; and advised more attention should be paid to soil water properties (Vanuytrecht et al 2014a;Paredes et al 2014;Pogson et al 2012) and soil types (Singh et al 2013). …”
Section: In-season Biomass Developmentmentioning
confidence: 99%
“…In this regard, some studies highlighted the importance of accurate modification of the crop growth parameters to increase the performance of the model (Zeleke et al 2011;Todorovic et al 2009). Several sensitivity analyses have shown the importance of soil water characteristics and available soil water for accurate crop growth and yield simulation under water stress; and advised more attention should be paid to soil water properties (Vanuytrecht et al 2014a;Paredes et al 2014;Pogson et al 2012) and soil types (Singh et al 2013). …”
Section: In-season Biomass Developmentmentioning
confidence: 99%
“…Gridded spatial data are used as parameter inputs and outputs in all kinds of spatial models, including ecological, meteorological and hydrological (Fischer and Wang, 2011;Pogson et al, 2012;Yang et al, 2008). The spatial detail, or resolution, of data affects how well they represent reality, as well as how accurately they can be combined with other spatial data within models to make predictions.…”
Section: Introductionmentioning
confidence: 99%
“…3). In a similar type of study, Pogson et al (2012) drove a miscanthus growth model with different meteorological and soil data sets, and also found that changes in several input variables, rather than individual ones, caused variations in simulated yields.…”
Section: Multi-scale Analysis At Individual Evaluation Sitesmentioning
confidence: 93%
“…However, most sensitivity analysis methods focus on single parameters rather than groups of covarying values, such as when entire input data sets are replaced (e.g. Pogson et al, 2012). More important than the methods used is the requirement that data independent of model development and calibration be used for evaluation and that statistics are appropriate to output variables of interest.…”
Section: Introductionmentioning
confidence: 98%